Hegemonic Formation in Post-Javanese Indonesian Society - Aprinus Salam (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
In society, there are various structured power relations that connect individuals who share certain interests and objectives. In these power relations, hegemony plays a significant role. Hegemony is the most important notion in the Marxist tradition, especially as it is conceptualized by Gramsci. This paper tries to re-read the issue of hegemony in the context of ideological contestation in Javanese society in Indonesia. The problem will be examined based on post-Marxist theory, especially as it relates to the demolition of the strong order of capitalism. Based on the results of the study, it can be concluded that hegemony forms itself in layers. The layers influence each other so that there is one area of hegemonic intersection. In Javanese society these days, there is a “competition,” especially in Yogyakarta, to return, feel, and become more Javanese than others. The implication is that there are parties who feel more Javanese than others. This case in this study is referred to as the post-Javanese society. However, in the intersection area, there are all-powerful puppeteers.